I survived : Hurricane Katrina, 2005 - Ball, Georgia (I survived (Graphic novel series), 2022)
With Hurricane Katrina bearing down on New Orleans, Louisiana, Barry Tucker and his family attempt to evacuate before it hits their home, but when his little sister gets sick, they are forced to wait out the storm. Things go from bad to worse when the levees breaks, and the floodwaters rise, separating Barry from his family. He rescues his neighbor's dog, Cruz, and the two must find a way to survive the storm together.